Differences in Compositions of Gut Bacterial Populations and Bacteriophages in 5–11 Year-Olds Born Preterm Compared to Full Term - Jayasinghe, Thilini N.; Vatanen, Tommi; Chiavaroli, Valentina; Jayan, Sachin; McKenzie, Elizabeth J.; Adriaenssens, Evelien; Derraik, José G. B.; Ekblad, Cameron; Schierding, William; Battin, Malcolm R.; Thorstensen, Eric B.; Cameron-Smith, David; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Preterm infants are exposed to major perinatal, post-natal, and early infancy events that could impact on the gut microbiome. These events include infection, steroid and antibiotic exposure, parenteral nutrition, necrotizing enterocolitis, and stress. Studies have shown that there are differences in the gut microbiome during the early months of life in preterm infants. We hypothesized that differences in the gut microbial composition and metabolites in children born very preterm persist into mid-childhood. Participants were healthy prepubertal children aged 5–11 years who were born very preterm (≤32 weeks of gestation; n = 51) or at term (37–41 weeks; n = 50). We recorded the gestational age, birth weight, mode of feeding, mode of birth, age, sex, and the current height and weight of our cohort. We performed a multi'omics [i.e., 16S rRNA amplicon and shotgun metagenomic sequencing, SPME-GCMS (solid-phase microextraction followed by gas chromatography-mass spectrometry)] analysis to investigate the structure and function of the fecal microbiome (as a proxy of the gut microbiota) in our cross-sectional cohort. Children born very preterm were younger (7.8 vs. 8.3 years; p = 0.034), shorter [height-standard deviation score (SDS) 0.31 vs. 0.92; p = 0.0006) and leaner [BMI (body mass index) SDS −0.20 vs. 0.29; p < 0.0001] than the term group. Children born very preterm had higher fecal calprotectin levels, decreased fecal phage richness, lower plasma arginine, lower fecal branched-chain amino acids and higher fecal volatile (i.e., 3-methyl-butanoic acid, butyrolactone, butanoic acid and pentanoic acid) profiles. The bacterial microbiomes did not differ between preterm and term groups. We speculate that the observed very preterm-specific changes were established in early infancy and may impact on the capacity of the very preterm children to respond to environmental changes.